The Effect of E-Service Quality on Interest in Retaking Online Training at Skill Academy - Hadithya, Riyan (Yayasan Pendidikan Belajar Berdikari, 2023)
This research was conducted because there are many education technology service providers who provide their services and services to assist the community in developing their abilities so that they can be further improved and in accordance with current needs. User satisfaction is the most important component in a service, thus generating user interest to re-take courses and training at skill academy. This study aims to analyze the impact of e-service quality on interest in re-entering online training at the Skill Academy. The population of this study are consumers who have used and attended online training on the Skill Academy application or website. The sampling technique used in this study was Non-Probability Sampling with a purposive sampling method with a total sample of 40 respondents. The analytical method used in this study is simple linear regression analysis with a significance level of 5%. The results of the analysis of e-service quality on repurchase intention show that the e-service quality variable has a positive and significant effect on repurchase intention.